2008
DOI: 10.1063/1.2983648
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport properties of wafer-fused p-GaAs/n-GaN heterojunctions

Abstract: GaAs/GaN pn heterojunction diodes have been fabricated by direct wafer fusion and characterized by capacitance-voltage (C-V) measurements and temperature dependent current-voltage (I-V) measurements. The wafer-fused pn diode showed a good rectifying behavior, but a small turn-on voltage was observed, which was attributed to defect-assisted tunneling-recombination. The flat-band voltage extracted from C-V is around 0.46 V, much smaller than the built-in voltage calculated for an ideal GaAs/GaN pn heterojunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…For n + -GaAs/p-Si junctions, ܳ ௧ and ܳ ீ௦ are expressed as [9] respectively. ܳ ௌ is simply given by ܳ ௌ = െ‫ܰݍ‬ ଶ ‫ݓ‬ ଶ .…”
Section: Theoretical Analysis Using Cnl Modelmentioning
confidence: 99%
“…For n + -GaAs/p-Si junctions, ܳ ௧ and ܳ ீ௦ are expressed as [9] respectively. ܳ ௌ is simply given by ܳ ௌ = െ‫ܰݍ‬ ଶ ‫ݓ‬ ଶ .…”
Section: Theoretical Analysis Using Cnl Modelmentioning
confidence: 99%
“…3(b)) is lower than V OC of the InGaP single junction cell (1.35 V). The disagreement is possibly explained by a potential barrier at the p-GaAs/n-GaN interface due to the valence band discontinuity between the two materials, which is assumed to be 1.6-1.7 eV in the ideal junctions [22]. The performance of the tandem cells might be deteriorated by the potential barrier.…”
Section: Cell Characterizationmentioning
confidence: 99%
“…In actual tandem cells, there could occur (i) the potential modulation due to the photo excited carriers in InGaP cells and (ii) the formation of the leak path across the bonding interface due to the bonding process [22]. The impact of the potential barrier is reduced in both schemes.…”
Section: Cell Characterizationmentioning
confidence: 99%
“…However, high-temperature annealing is necessary to form junctions in wafer-fused bonding. 16,17) Such a high-temperature process might cause the degradation of crystal qualities due to the evaporation of arsenic atoms or mechanical defects due to the difference between the thermal expansion coefficients of bonded substrates. In SAB, substrate surfaces are activated by the fast atom beams of Ar prior to bonding without heating.…”
Section: Introductionmentioning
confidence: 99%
“…23,24) Lian et al fabricated GaAs=GaN p-n heterojunction diodes by wafer-fused bonding and characterized their electrical properties by capacitance-voltage (C-V ) and temperaturedependent current-voltage (I-V ) measurements. 17) They presumed that the band alignment was of type II. Kim et al also reported on GaAs=GaN p-n heterojunction diodes, 3) which were fabricated by bonding GaAs and GaN substrates to each other after their surfaces were activated by the O 2 plasma.…”
Section: Introductionmentioning
confidence: 99%